An examination of how lecturers' pedagogical beliefs are reflected in their use of ICTs in teaching practice : a case for Africa University EMBA lecturers - Chipunza, Unity (School of Education, 2014)
In the study, six lecturers were surveyed to determine their pedagogical beliefs. The findings of the lecturers' beliefs survey indicated that no one lecturer strictly held one belief construct. They instead held a mixture of the beliefs and the distinction was in the actual mix.